2023
DOI: 10.1007/s00382-023-06853-0
|View full text |Cite
|
Sign up to set email alerts
|

Convection-permitting climate simulations for South America with the Met Office Unified Model

Abstract: We present the first convection-permitting regional climate model (CPRCM) simulations at 4.5 km horizontal resolution for South America at near-continental scale, including full details of the experimental setup and results from the reanalysis-driven hindcast and climate model-driven present-day simulations. We use a range of satellite and ground-based observations to evaluate the CPRCM simulations covering the period 1998–2007 comparing the CPRCM output with lower resolution regional and global climate model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 80 publications
1
26
0
Order By: Relevance
“…As observed by Halladay et al (2023), the UKMO CPRCM-PD (and the GCM) simulation is wetter than the CPRCM-ERA (and RCM). This difference is also evident when comparing the precipitation rate anomalies during simulated cloud band events.…”
Section: Cloud Band Simulation During the Core Rainfall Seasonmentioning
confidence: 64%
See 3 more Smart Citations
“…As observed by Halladay et al (2023), the UKMO CPRCM-PD (and the GCM) simulation is wetter than the CPRCM-ERA (and RCM). This difference is also evident when comparing the precipitation rate anomalies during simulated cloud band events.…”
Section: Cloud Band Simulation During the Core Rainfall Seasonmentioning
confidence: 64%
“…This suggests that CPRCMs are more efficient in consuming energy and producing precipitation than their parent parametrised models. Thus, biases in the precipitation intensity are likely associated with explicitly resolving the convection and the interplay with the model's configurations and other parametrisations, such as cloud microphysics schemes, as suggested by Halladay et al (2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar larger future increases in short-duration precipitation extremes in CPRCMs were found in the UK, US and Europe (see Kendon et al, (2021) for more details). Despite the CPRCM benefits, which are mainly at sub-daily scales and are often referred to as the added value (Lucas-Picher et al, 2021), these models still have known biases when evaluated against observed distributions of rainfall: mainly that the heavy rainfall at grid-scale can be too intense Halladay et al, 2023;Kendon et al, 2021). Rowell and Berthou (2023) found that most regions (apart from for large mountains, and to lesser extent coastlines and urban areas) show a closer match between model and observations when spatial aggregation of the 4.5km CPRCM data to 25 km is performed before the rainfall analysis.…”
Section: Introductionmentioning
confidence: 99%